The Jews of modern France - Hyman, Paula, 1946-2011 (Jewish communities in the modern world, 1998)
The book explores the complex encounter of France and its Jews from just before the revolution to the present. The author shows how French Jews have embraced the opportunities of integration and acculturation, redefined their identities, and adapted their Judaism to the pragmatic and ideological demands of the time.